Environmental life-cycle assessment of waste-coal pellets production - Hanak, Dawid P. (Oxford University Press, 2021)
Industrial decarbonization is crucial to keeping the global mean temperature <1.5°C above pre-industrial levels. Although unabated coal use needs to be phased out, coal is still expected to remain an important source of energy in power and energy-intensive industries until the 2030s. Decades of coal exploration, mining and processing have resulted in ~30 billion tonnes of waste-coal tailings being stored in coal impoundments, posing environmental risks. This study presents an environmental life-cycle assessment of a coal-processing technology to produce coal pellets from the waste coal stored in impoundments. It has been shown that the waste-coal pellets would result in the cradle-to-gate global warming of 1.68–3.50 kgCO2,eq/GJch, depending on the source of electricity used to drive the process. In contrast, the corresponding figure for the supply of conventional coal in the US was estimated to be 12.76 kgCO2,eq/GJch. Such a reduction in the global-warming impact confirms that waste-coal pellets can be a viable source of energy that will reduce the environmental impact of the power and energy-intensive industries in the short term. A considered case study showed that complete substitution of conventional coal with the waste-coal pellets in a steelmaking plant would reduce the greenhouse-gas emissions from 2649.80 to 2439.50 kgCO2,eq/tsteel. This, in turn, would reduce the life-cycle greenhouse-gas emissions of wind-turbine manufacturing by ≤8.6%. Overall, this study reveals that the use of waste-coal pellets can bring a meaningful reduction in industrial greenhouse-gas emissions, even before these processes are fully decarbonized.
Keywords: coal impoundments; LCA; environmental-impact assessment; renewable energy; decarbonization; fossil fuels